Unguided web-based brief intervention with genetic risk education to reduce unhealthy alcohol consumption in Japan: Protocol for a randomized controlled trial - Yuki Kono; Mai Tanaka-Sahker; Shino Kikuchi; Yan Luo; Masatsugu Sakata; Ryuhei So; Tamara L. Wall; Toshi A. Furukawa; Ethan Sahker (PLoS ONE, 2026)
Background Alcohol consumption is a major global contributor to morbidity and mortality and is a well-established risk factor for multiple cancers. Acetaldehyde, a toxic metabolite of ethanol, is a causal factor in alcohol-related esophageal cancer. A substantial proportion of the Japanese population carries the aldehyde dehydrogenase 2*2 ( ALDH2*2) allele, which impairs ALDH2 enzymatic activity and increases acetaldehyde exposure, thereby elevating esophageal cancer risk. Among individuals with the ALDH2*2 allele, cancer risk demonstrates a clear dose–response relationship with alcohol consumption, with relative risks reported to be up to four times the relative risk, compared to non-carriers. Objectives This project aims to evaluate the efficacy of an unguided, web-based brief intervention (BI) incorporating genetic cancer-risk education to reduce alcohol consumption in a randomized controlled trial. Methods Participants will be recruited online between March and July 2026 through a Japanese research panel company. Eligibility will include moderate alcohol use and probable ALDH2*2 allele status. Participants will be randomized to either an experimental condition or a sham educational control. The experimental group will receive an unguided, web-based, brief video intervention providing information on genetic cancer risks associated with alcohol consumption and the benefits of reducing drinking. The primary outcome will be mean past-4-week alcohol quantity at the 3-month endpoint. Secondary outcomes will include alcohol use in grams, alcohol-related severity, motivation to change, health-knowledge retention, participant satisfaction, and quality of life. Assessments will occur at baseline and at 1, 2, and 3 months post-randomization via a secure web portal. Discussion This intervention is expected to reduce unhealthy alcohol use at low implementation cost by leveraging personalized genetic risk information as a motivational mechanism in the general population. Additional between-group differences are anticipated across secondary alcohol-related outcomes. Trial Registration: This trial registered on 11/28/2025 in the University Hospital Medical Information Network Clinical Trials Registry (UMIN000058012).